Choice of Antibiotics for the Treatment of Orthopedic Infection Caused by Gram-Positive Pathogens, Based on a 12-Year Follow-Up. Part 1: Penicillins, Cephalosporins, Glycopeptides, Oxazolidinones, Fusidic Acid, Rifampicin - Alina R. Kasimova; Svetlana A. Bozhkova; Olga S. Tufanova; Ekaterina M. Gordina; Anton N. Gvozdetsky; Anna N. Rukina; Rashid M. Tikhilov (Travmatologiâ i Ortopediâ Rossii)
Background. Antibacterial agents are used in orthopedic practice to prevent surgical site infections, as well as for empirical and etiotropic antibacterial therapy. Each of the groups of antibacterial agents has specific indications for use and limitations that determine their role in empirical and etiotropic treatment regimens for musculoskeletal infections.